Social network and villagers’ willingness to adopt residential rooftop PV products: A multiple mediating model based on TAM/PR theory - Wang, Weidong; Guan, Xieyue; Jin, Shunlin; Wang, Xiaonan; Qin, Xue; Lu, Na; Zhu, Guyu; Li, Dingding (Frontiers in Environmental Science, 2022)
Facing the promise of “carbon neutrality” and “carbon peak”, China’s vast rural areas will be the main front of energy conservation and emission reduction in the future. From the perspective of social capital, this paper combined TAM and perceived risk theory to construct a hypothesis model. Based on 617 rural survey data, structural equation model was used to reveal the influencing factors of the willingness to adopt residential rooftop PV products in rural China. The results show that : (1) social network has a significant impact on the willingness of villagers to adopt rooftop PV products. (2) Perceived usefulness, perceived ease of use and perceived risk play multiple mediating roles. (3) The parallel mediating effect of villagers’ perceived risk on the relationship between social network and adoption intention is much higher than the other two paths. (4) The chain mediating effect of perceived risk and perceived ease of use on the relationship between social network and villagers’ adoption intention is much higher than the other two paths. This study provides rich policy implications for rural renewable energy promotion and energy transition in China and other developing countries.